If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 = 5(3x + -3) Reorder the terms: 75 = 5(-3 + 3x) 75 = (-3 * 5 + 3x * 5) 75 = (-15 + 15x) Solving 75 = -15 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 75 + -15x = -15 + 15x + -15x Combine like terms: 15x + -15x = 0 75 + -15x = -15 + 0 75 + -15x = -15 Add '-75' to each side of the equation. 75 + -75 + -15x = -15 + -75 Combine like terms: 75 + -75 = 0 0 + -15x = -15 + -75 -15x = -15 + -75 Combine like terms: -15 + -75 = -90 -15x = -90 Divide each side by '-15'. x = 6 Simplifying x = 6
| (3p-7)+(5p-7)= | | 4x-1=9+x | | -5+13y+8=14+15y-21 | | sqrt(x)=16 | | (-3)(-3)+4[18+(12-20)]= | | 4=2(2x-4) | | -5+2x=6 | | 19=3g+1 | | 136=4(5x+4) | | 6+4u=10 | | 4x-20+x+50=180 | | 4x-40+60= | | 5+s=6 | | 8x-14=-5x+12 | | 48=2(5x+4) | | 2x+3+x+6=90 | | 3k-11=5 | | 6x=20-x+4 | | 2y+14x=28 | | 5t^2+7t-8=0 | | 5x/7-8=10 | | 3m-2=2m-1 | | 16=2+2d | | 9x+1-3x=7x-9+x | | a+5=3a-5 | | 128=4(5x+2) | | 15=24-4x | | 5(4-x)=2x-1 | | -4n-12=-2(n+3) | | 6x+6=26-2x | | 8x-14=5x+12 | | 225x^2+4x+3=0 |